Rupture and liminality: Experiences of Scotland's refugee population during a time of COVID-19 lockdown - Nicole Vidal; Olivia Sagan; Alison Strang; Gianluca Palombo (Elsevier, 2023)
The disruption caused by the COVID-19 pandemic had profound effects on refugees. In migrating to seek safety, refugees demonstrate resilience, resourcefulness and the ability to adapt to stressful situations. However, social distancing and self-isolation measures greatly impacted these individuals, as they stand to risk the most from interruptions to integration. In this paper, we examine the implications of increased loneliness and isolation for refugees' experiences with integration. We argue, using original interview data, that the demands placed on some refugees through extremely harsh circumstances can leave many even more vulnerable, as was evident in extreme during the COVID-19 lockdowns. The findings of this study pertain to the refugee pandemic experience in relation to loneliness, hopelessness and, more so: agency, resilience and post-traumatic growth. In recognising that rupture and liminality are intrinsically linked to feelings of loneliness, mental wellbeing, or its erosion, the paper demonstrates the complexity of loneliness and its potential to cause long-term damage to mental and physical health. Our findings suggest the importance of an approach to integration that recognises the unique needs of refugees. Where emotionally supportive social networks are weak or absent, it must be a priority to enable meaningful connections with other trusted human beings.